2016
DOI: 10.1016/j.renene.2016.05.079
|View full text |Cite
|
Sign up to set email alerts
|

Designing renewable energy auctions for India: Managing risks to maximize deployment and cost-effectiveness

Abstract: a b s t r a c tWe examined 20 renewable energy auctions in India and elsewhere to answer two questions: first, have auctions been effective; and second, how can they be designed to achieve India's renewable energy targets? The significant contributions lie in the larger sample size, use of secondary and primary research, and application of quantitative and qualitative analysis. We found that auctions are almost always cost-effective, with savings up to 58% from baseline feed-in tariffs. However, auctions may n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Nevertheless, mostly because of the random use made of these schemes around the world compared with feed-in-tariffs (FITs) and renewable portfolio standards (RPS), far too little attention has been paid to RES auction schemes. As observed, the opportunity to control the costs of RES support and deployment volumes as well as recent positive results achieved in some countries explain a renewed interest in auction programmes both at government and scientific level as a means for procuring supplies of renewable energy (Becker and Fischer, 2013;Cozzi, 2012;European Commission, 2013;IRENA, 2013;Kreycik et al, 2011;Shrimali et al, 2016).…”
Section: Literature Backgroundmentioning
confidence: 94%
See 2 more Smart Citations
“…Nevertheless, mostly because of the random use made of these schemes around the world compared with feed-in-tariffs (FITs) and renewable portfolio standards (RPS), far too little attention has been paid to RES auction schemes. As observed, the opportunity to control the costs of RES support and deployment volumes as well as recent positive results achieved in some countries explain a renewed interest in auction programmes both at government and scientific level as a means for procuring supplies of renewable energy (Becker and Fischer, 2013;Cozzi, 2012;European Commission, 2013;IRENA, 2013;Kreycik et al, 2011;Shrimali et al, 2016).…”
Section: Literature Backgroundmentioning
confidence: 94%
“…Opportunities for empirical assessments are restricted by the limited use of auctions for RES-E support and the lack of suitable data on tenders. Reviews of different countries' experiences can be found in recent works such as Azuela et al (2014); Barroso and Batlle (2011); (Eduardo and Parente, 2013) regarding the Brazilian case; del Río (2016b); Eberhard (2014); Montmasson-Clair and Ryan (2014); Toke (2015) regarding the South-African auctions; Shrimali et al (2016) regarding the Indian experience; Mastropietro et al (2014); Moreno et al (2010) regarding the South American experiences; del Río (2016a); Fitch-Roy and Woodman (2016); Förster (2016); Kitzing and Wendring (2015); Noothout and Winkel (2016); Steinhilber (2016a); Tiedemann (2015); Tiedemann et al (2016) respectively for Portugal, UK, France, Denmark, Netherlands, Germany, and Italy;and Steinhilber (2016b) regarding the onshore wind concession auctions in China. As regards RES technologies in particular, onshore wind auctions, either technology-specific or all-encompassing, have been held in most of the countries analysed.…”
Section: Literature Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…A feature of India's recent success has been its use of reverse auctions to secure low-price contracts for solar and wind electricity generation (Shrimali et al, 2016). One of our conclusions is that there is scope for Indonesia to launch a special round of large-scale procurement auctions of its own.…”
Section: Introductionmentioning
confidence: 92%
“…Given the pragmatic relevance and novelty of RE auctions at the policy level, the majority of literature on auction design and implementation has so far been coming from so-called "gray" literature by institutions such as the International Renewable Energy Agency (IRENA), GIZ, and the World Bank (IRENA, 2012;IRENA & CEM, 2015;Lucas, Ferroukhi, & Hawila, 2013;Tietjen, Blanco, & Pfefferle, 2015). The past few months have however seen recent scholarly publications on specific auction design aspects for energy projects, such as risk mitigation (Shrimali, Konda, & Farooquee, 2016), volume control, qualification requirements, and penalties (Gephart et al, 2017;Kreiss, Ehrhart, & Haufe, 2016). Whereas the IPP success factor literature was primarily focused at the country and project level, much of the literature on auctions is focused on the level in between: the program (design) level.…”
mentioning
confidence: 99%